The Utilization of Social Media in Grounding the Recitation of the Qur'an in Recitation of Mujawwad - Adistian Adistian; Mansyur Mansyur; Ahmad Ahmad; Abdul Fattah; St Muthahharah; Mursyid Fikri (Prodi PGMI STIT Sunan Giri Bima, 2026)
This study discusses the use of social media in grounding the recitation of the Qur'an in mujawwad recitation: a study of Islamic education in the digital era. The development of social media has provided a new space for the community to learn, preach, and spread Islamic values. Qur'an recitation that was previously more widely studied in mosques, Islamic boarding schools, and taklim assemblies is now also developing through digital platforms such as YouTube, TikTok, Facebook, and Instagram. This study aims to analyze the role of social media in grounding mujawwad recitation and examine its implications for Islamic education. This research uses a library research method by collecting data from books, journals, scientific articles, and other relevant references. Data collection techniques are carried out through editing, organizing, and finding, while data analysis is carried out through data reduction, data presentation, and verification. The results of the study show that social media plays a strategic role as a means of digital da'wah, a medium for learning the Qur'an, and strengthening people's Qur'anic literacy. Mujawwad recitations spread through social media are able to increase the interest of the public, especially the younger generation, to listen, learn, and love the Qur'an. From the perspective of Islamic education, the use of social media reflects the dimensions of ta'lim, tarbiyah, and ta'dib. However, social media cannot replace the role of teachers in learning mujawwad recitation which requires direct guidance. Therefore, social media can be an effective instrument of Islamic education and da'wah of the Qur'an if used wisely, educationally, and while maintaining the glory of the Qur'an.